Situs ambiguous with duodenal atresia in a neonate: A case report with literature review - Edan, Obay (Journal of Neonatal Surgery, 2024)
Background: Situs ambiguous is a rare congenital anomaly characterized by an unusual and irregular distribution of the major visceral organs and vessels within the chest and abdomen. In this condition, the organs are arranged in a way that cannot be classified as either situs inversus or situs solitus. We report this case due to the rarity of this anomaly and its uncommon association with duodenal atresia in a neonate. Case Presentation: A full-term newborn female presented with repeated bilious vomiting and failure to pass meconium for five days. An erect abdominal X-ray revealed a double-bubble sign in the left hemiabdomen, and a CT scan confirmed an abnormal relationship between the liver and stomach. Operative exploration confirmed the diagnosis of situs ambiguous with duodenal atresia, which was treated with a diamond duodenoduodenostomy. Conclusion: Situs ambiguous is a rare variant of situs anomaly with few reported cases worldwide. It has two subtypes: left and right isomerism, based on the anatomy of the spleen. Clinically, it can present with features of intestinal obstruction when associated with duodenal atresia.